EFFORT TO IMPROVE CONCEPTUAL UNDERSTANDING OF NATURAL RESOURCE-RELATED ECONOMIC ACTIVITIES THROUGH THE APPLICATION OF CIRCUIT LEARNING MODEL - Riski Fitriana Sativa; Soegiyanto Soegiyanto; Sadiman Sadiman (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The objective of this research is to investigate the improvement of conceptual understanding of natural resource-related economic activities through the application of Circuit Learning model. This research used classroom action research with two cycles. Its data were collected through in-depth interview, observation, test, and documentation. They were validated by using content validity and data collection technique triangulation. The data were analyzed by using the Miles & Huberman’s interactive model of analysis. The result of the research shows that prior to the treatment 5 out of 31 students (16.13%) fulfilled the minimal learning completeness criterion of 70. Following the treatments, the number of the students who fulfilled the criterion was 13 students (42%) in Cycle I and 26 (83.87%) in Cycle II respectively. Thus, the Circuit Learning model can improve the conceptual understanding of natural resource-related economic activities of the students in Grade IV of State Primary School Karangasem IV No. 204 of Surakarta in Academic Year 2017/2018.